Le rôle de l'État quant aux grandes orientations en matière énergétique - Garant, Patrice (Les Cahiers de droit, 1983)
The State, whether at the federal or provincial levels, is deeply involved in the determination of the orientation of energy policy. It assumes a major role as « planner », « regulator », « producer » and « distributor ». One has first to take into account the constitutional context, that is the division of powers outlined in our Constitutional Acts of 1867 and 1982. There is now a complex balance of power which, although it appears to satisfy all parties, require considerable dialogue to work out. This is called at home and in other federal countries « cooperative federalism », with some federal para-mountcy nevertheless.